Gender and culture in psychology : theories and practices - Magnusson, Eva, 1947-; Marecek, Jeanne, 1946- (New York : Cambridge University Press, 2012)
'Gender and Culture in Psychology introduces readers to new approaches to the psychological study of gender that bring together feminist psychology, socio-cultural psychology, discursive psychology and critical psychology. It presents research and theory that embed human action in social, cultural and interpersonal contexts. The book provides conceptual tools for thinking about gender, social categorization, human meaning and culture. It also describes a family of interpretative research methods, which focus on rich talk and everyday activities, and provides a close-in view of how interpretative research proceeds. The latter portion of the book showcases innovative projects in the psychology of gender that investigate topics of concern to scholars and feminist activists: young teens' encounters with heterosexual norms; male-female couples' negotiating the sharing of housework and childcare; sexual coercion and violence in male-female relationships; the cultural politics of women's weight and eating concerns; psychiatric labelling of psychological suffering; and feminism in psychotherapy'--
Includes bibliographical references and index.
Keywords: Feminism -- Psychological aspects; Gender identity -- Psychological aspects; Culture -- Psychological aspects